Edukasi Pemanfaatan PLTS untuk Penerangan Jalan Umum Di Desa Cilatak Kecamatan Ciomas Kabupaten Serang Banten - Kartika Tresya Mauriraya; Rio Afrianda; Alex Fernandes; Andi Makkulau; Dewi Purnama Sari; Novi Kurniasih (Terang, 2020)
This community partnership program aims to help provide understanding to the public on the use of PLTS for Public Road Lighting in Cilatak Hamlet, Sukadana Village, and encourage and utilize environmentally friendly small-scale energy, which is very suitable for areas not yet covered by the PLN electricity grid or for energy efficiency on a small scale.